On the pivotal role of water potential to model plant physiological processes. Issue 1 (18th January 2022) - De Swaef, Tom; Pieters, Olivier; Appeltans, Simon; Borra-Serrano, Irene; Coudron, Willem; Couvreur, Valentin; Garré, Sarah; Lootens, Peter; Nicolaï, Bart; Pols, Leroi; Saint Cast, Clément; Šalagovič, Jakub; et al.
Abstract: Water potential explains water transport in the soil–plant–atmosphere continuum (SPAC), and is gaining interest as connecting variable between 'pedo-, bio- and atmosphere'. It is primarily used to simulate hydraulics in the SPAC, and is thus essential for studying drought effects. Recent implementations of hydraulics in large-scale terrestrial biosphere models (TBMs) improved their performance under water-limited conditions, while hydraulic features of recent detailed functional–structural plant models (FSPMs) open new possibilities for dissecting complex traits for drought tolerance. These developments in models across scales deserve a critical appraisal to evaluate its potential for wider use in FSPMs, but also in crop systems models (CSMs), where hydraulics are currently still absent. After refreshing the physical basis, we first address models where water potential is primarily used for describing water transport along the transpiration pathway from the soil to the leaves, through the roots, the xylem and the leaf mesophyll. Then, we highlight models for three ecophysiological processes, which have well-recognized links to water potential: phloem transport, stomatal conductance and organ growth. We identify water potential as the bridge between soil, root and shoot models, as the physiological variable integrating below- and above-ground abiotic drivers, but also as the link between water status and growth. Models making these connections enable identifying crucial traits for ecosystem resilience to drought and for breeding towards improved drought tolerance in crops. Including hydraulics often increases model complexity, and thus requires experimental data on soil and plant hydraulics. Nevertheless, modelling hydraulics is insightful at different scales (FSPMs, CSMs and TBMs).